Elevated preradiotherapy serum lactate dehydrogenase predicts distant metastasis for lymphoepithelial carcinoma of major salivary gland following postoperative radiotherapy. Issue 12 (24th August 2022) - Yan, Wenbin; Liu, Yang; Shen, Chunying; Yi, Junlin; Ou, Xiaomin; Hu, Chaosu
Abstract: Background: To evaluate the predicting factors associated with distant metastasis (DM) for lymphoepithelial carcinoma of salivary gland (LECSG) following postoperative radiotherapy (PORT). Methods: We retrospectively collected 160 eligible patients from two cancer institutions. The DM rate was evaluated using competing risk method. Results: The median follow‐up time was 65.6 months. Elevated preradiotherapy serum LDH (ratio >0.5) ( p = 0.006) and N classification (N2‐3) ( p = 0.001) were independently associated with DM for the LECSG. After the risk stratification, the high‐risk subgroup was defined as the patients presented higher risk score (score >0), whereas 5‐year cumulative incidence of DM in the high‐ and low‐risk group was 30.9% and 6.0%, respectively ( p < 0.001). Moreover, a significantly worse overall survival (OS) was observed in the high‐risk patients compared with the low‐risk subgroup (5‐year OS: 83.9% vs. 97.8%, p = 0.006). Conclusion: Elevated preradiotherapy serum LDH could serve as a predictive factor for DM in the LECSG following PORT.